ANALISA DAMPAK LALU LINTAS GUMAYA TOWER HOTEL DI JALAN GAJAH MADA SEMARANG - Nur Hairani L.; Fachrul Rizka; Sri Prabandiyani Retno Wardani; Ismiyati Ismiyati (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2013)
Nowadays the progress of Semarang city is getting rapid, many shop centers rises in golden triangle areas, that are (St. Gajah Mada, St. Pemuda and St. Pandanaran). Most of people use their car or motorbike to do their activities through those streets. This condition caused the higher mobility each year and makes parking lots become important thing in transportation system. The problems about parking lots is important to research. The necessary of parking lot should be available. The bigger traffic volume makes bigger necessary of parking lot. If it does not enough, cars may take the spaces beside of road to park, and this caused some disruptions to others. This research will analyze the effects of traffic of Gumaya Tower Hotel which located at Gajah Mada street number 59-61 Semarang. Maximum accumulation method and queue theory are used in this research. Prymary data which necessary such as amount of car, time-parking, and service system. Whereas for secondary data to analyze traffic growth is car ownership data in semarang. The conclusion of this research is that effect of traffic in gumaya tower hotel area caused by the entrace and exit of hotel that not really good so can offend people who use gajah mada street.